2012
DOI: 10.1100/2012/105712
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring BOD : COD Ratio of Dairy Milk Industrial Wastewaters in BOD Analysis by Formulating a Specific Microbial Seed

Abstract: BOD (Biochemical oxygen demand) is the pollution index of any water sample. One of the main factors influencing the estimation of BOD is the nature of microorganisms used as seeding material. In order to meet the variation in wastewater characteristics, one has to be specific in choosing the biological component that is the seeding material. The present study deals with the estimation of BOD of dairy wastewater using a specific microbial consortium and compares of the results with seeding material (BODSEED). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Pseudomonas and Bacillus species with high-fat degradation effectiveness had been isolated from wastewater sources (Loperena et al 2009). While the former genera were mainly associated with xenobiotic cleanup of industrial wastes (Golovleva et al 1992), both were proposed to be used to improve wastewater treatment process (Dhall et al 2012;Loperena et al 2006Loperena et al , 2009. Consistently, strains G13, G20, G21 and G24, isolated from a commercial product (Glensol 3901), belong to Bacillus genera.…”
Section: Discussionmentioning
confidence: 95%
“…Pseudomonas and Bacillus species with high-fat degradation effectiveness had been isolated from wastewater sources (Loperena et al 2009). While the former genera were mainly associated with xenobiotic cleanup of industrial wastes (Golovleva et al 1992), both were proposed to be used to improve wastewater treatment process (Dhall et al 2012;Loperena et al 2006Loperena et al , 2009. Consistently, strains G13, G20, G21 and G24, isolated from a commercial product (Glensol 3901), belong to Bacillus genera.…”
Section: Discussionmentioning
confidence: 95%
“…They usually contain large fraction of organic compounds that act as a substrate for microorganisms when they released into water resources. Dairy wastewater is of great concern because of containing high-carbonaceous and nitrogenous compounds (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The investigators identified a microorganism that produced comparable BOD response profiles by two methods of BOD determination, the conventional bioassay and using BOD sensors. In a study, Dhall et al [10], compared BOD to COD ratios of inoculum of an isolated consortium of microbes to the BOD to COD ratios of a commercially sold seed. The study yielded BOD to COD ratios of O.5 -0.6 for the commercial seed and 0.78 -0.8 for the isolated bacteria strains.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that BOD to COD ratios with the isolated consortium were more significant. Furthermore, the researchers [10] examined the effect of using a specific microbial consortium compared to commercial seeding material (BODSEED) on the BOD of dairy wastewater. They isolated bacterial strains from 5 different sources and screened by the conventional BOD method.…”
Section: Introductionmentioning
confidence: 99%